Association of serum iron status with MASLD and liver fibrosis - Wenying Guo; Ting Weng; Yufei Song (PLoS ONE, 2025)
Background The MASLD proposal updates and supplements the previous definition of NAFLD, making it more suitable for addressing the current understanding of chronic liver diseases. This study aims to investigate the potential association between serum iron status and the occurrence of MASLD and liver fibrosis. Methods An in-depth analysis was conducted using the 2017–2020 NHANES data. To assess the relationship between serum iron status and the prevalence of MASLD and liver fibrosis, we performed comprehensive data analysis. This approach accounts for multiple variables, enhancing the robustness and reliability of our results by reducing potential confounding factors. Results Our application of linear regression models provided significant insights through a comprehensive data analysis. Elevated serum ferritin, TIBC, and UIBC showed a distinct positive correlation with CAP, while only serum ferritin was positively correlated with LSM. Multivariate logistic regression analysis revealed that elevated levels of serum ferritin, TIBC, and UIBC were significantly associated with the occurrence of MASLD, whereas only serum ferritin showed a similar association with the occurrence of liver fibrosis. Conclusion This study highlights the significant positive correlation between elevated levels of serum ferritin, TIBC, and UIBC with CAP and the prevalence of MASLD. A similar relationship was observed between serum ferritin with LSM and the prevalence of liver fibrosis.